Supplementation of Glycine and Glucose into Egg Yolk Lactated Ringer Diluent on The Quality of Local Chicken Semen Stored at 5oC for 120 Hours - Junaedi, Junaedi; Isnaini, Nurul; Natsir, Muhammad Halim; Susilawati, Trinil (Jurnal Medik Veteriner, 2024)
The impact of supplementing glucose, glycine, or a combination of both in Ringer's lactate egg yolk base extender to preserve the quality of semen from local Indonesian chickens has not been previously investigated. This study aimed to examine the potential of glucose and glycine on chicken semen stored at 5°C for 120 hours. In this study, five local roosters were used. The parameters under observation included semen volume, odor, pH levels, consistency, color, mass movement, concentration, motility, viability, abnormality, plasma membrane integrity, chromatin degeneration, and acrosomal cap integrity. This study was conducted using a completely randomized design (CRD) with four treatments groups and 10 replication, i.e. T1 (control without supplementation), T2 (50 mM glucose), T3 (60 mM glycine), and T4 (a combination of 50 mM glucose and 60 mM glycine), respectively. In result, semen volume was 0.54 ± 0.17 mL/ejaculate, a milky white color, distinctive odor, thick consistency, good mass movement (++/+++), pH of 7.37 ± 0.23, motility of 91.50 ± 2.42%, plasma membrane integrity of 96.85 ± 0.96%, abnormality at 2.88 ± 0.77%, the concentration of 3.04 ± 0.3 billion/mL, and viability of 96.47 ± 1.71%. Following storage at 5°C for 120 hours, the motility, viability, abnormality, and acrosomal cap integrity of local chicken spermatozoa significantly different (p < 0.05) between T3 and T4 compared to T1 and T2 groups. Moreover, the integrity of the plasma membrane and chromatin degeneration in treatment T3 significantly different (p < 0.05) from T1, T2, and T4 groups. In conclusion, local chickens exhibited fair quality fresh semen both in macroscopic and microscopic evaluations. Furthermore, the combination of 60 mM glycine and 50 mM glucose into local chicken semen stored at 5°C for 120 hours effectively preserved motility and viability, minimized abnormality, maintained plasma membrane integrity, minimized chromatin degeneration, and retained acrosomal integrity.